Technologies of government : politics and power in the information age - Baez, Benjamin (Studies in the philosophy of education., 2014)
In this book, Baez examines a series of governmental "technologies" that he believes strongly characterize our present. The technologies that he addresses in this book are information, statistics, databases, economy, and accountability. He offers arguments about the role these technologies play in contemporary politics. Specifically, Baez analyzes these technologies in terms of (the sometimes oppositional) rationalities for rendering reality thinkable, and, consequently, governable. These technologies bear on the field of education, but also exceed it. So, while issues in education frame many of the arguments in this book, the book's also has usefulness to those outside of field of education.Specifically, Baez concludes that the governmental technologies listed above all are coopted by neoliberal rationalities rendering our lives thinkable and governable through an array of devices for the management of risk, using the model of the economy, and heavily investing in the uses of information, statistics, databases, and oversight mechanisms associated with accountability. Baez leaves readers with more questions than they might have had prior to reading the book, so that they may re-imagine their own present and future and thus their own forms of self-government.